Towards practical runtime verification and validation of self-adaptive software systems (2010)
Software validation and verification (V&V) ensures that software products satisfy user requirements and meet their expected quality attributes throughout their lifecycle. While high levels of adaptation and autonomy provide new ways for software systems to operate in highly dynamic environments, developing certifiable V&V methods for guaranteeing the achievement of self-adaptive software goals is one of the major challenges facing the entire research field. In this chapter we (i) analyze fundamental challenges and concerns for the development of V&V methods and techniques that provide certifiable trust in self-adaptive and self-managing systems; and (ii) present a proposal for including V&V operations explicitly in feedback loops for ensuring the achievement of software self-adaptation goals. Both of these contributions provide valuable starting points for V&V researchers to help advance this field.